Al-Mabadi’ Al-Khamsah dan Al-Kulliyah Al-Khams; Sebagai Konsep Penjamin Hak Kebebasan Beragama Berkeyakinan - Moch. Mukhlison; Muhammad Isnan (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
The case of intolerance and restrictions on the right to religious freedom is a never-ending discourse. That is because these cases still occur in Indonesia with such high numbers. In the last five years, data shows an increase in cases of intolerance and restrictions on religious freedom. In this condition, it turns out that the right to freedom of religion and belief has not provided benefits for minority groups. This paper tries to reveal how the rights to freedom of religion and belief are upheld by the norms of Human Rights and the State as the guarantor. This article also tries to reveal that even Islam with the teachings of tolerance and the concept of Al-Mabadi 'Al-Khamsah and Al-Kulliyah Al-Khams provide support for the creation of justice, peace and harmonious relations between humans.